Eco-Theology: Purification of Respect Against Du'a Ngga'e Ende-Lio Tribe - Nara, Marianus Angi; Sudhiarsa, Raymundus I Made; Yuniarto, Petrus (Universitas Tanjungpura, 2024)
Each culture has its unique approach to understanding the concept of safety, and the Ende-Lio culture on Flores Island, Indonesia, is no exception. In the Ende-Lio culture, the concept of salvation is known as